The Freedom Party and grand narrative - Kirişçioğlu, İlkay. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2018., 2018)
This thesis is about a political party in Turkish political history, the Freedom Party, founded by a group of displeased Democrat Party deputies in late 1955 as the result of longstanding intraparty struggles among some cliques. e ultimate crisis that led to the formation of the party was brought to surface when these displeased deputies gave a right to prove bill to the chair of the assembly in a move against their rivals which was backed by the party center before the fourth convention of the DP where a battle for the seats of the general administrative board was expected by public at the time. These DP deputies who resigned or expelled from their party formed the FP. Nevertheless, the party was a flash in the pan; it started to disappear after the 1957 elections which marked total destruction for the party with respect to its results. After this catastrophe, the center of the FP decided to unite with the Republican People’s Party at the end of 1958. This party, which was in existence for three years, has been regarded by researchers using a range of theories determined by grand narratives, that instrumentalized it. Contrary to these, this work suggests that the FP cannot be comprehensively understood based on metanarratives that discard the agencies and it focuses on the internal dynamics of the DP and the personal experiments of the figures of the FP to grasp the actual qualities of it beyond what the previous works suggest.
Keywords: Political parties -- Turkey -- History.; Turkey -- Politics and government -- 1918-1960.